Let's solve this problem step-by-step.
Explanation:
The method which we will be using to solve this problem will be simultaneous equations.
Let's first write down the two equations as follows:
Equation No. 1 -
5x + y = - 5
Equation No. 2 -
- 15x - 3y = 9
PROBLEM SOLVING METHOD NO. 1 -
We will first make ( y ) the subject in the first equation and solve accordingly.
Equation No. 1 -
5x + y = - 5
y = - 5 - 5x
From this, we will substitute the value of ( y ) from the first equation into the second equation to solve for ( x ) accordingly.
Equation No. 2 -
- 15x - 3y = 9
- 15x - 3 ( - 5 - 5x ) = 9
- 15x + 15 + 15x = 9
- 15x + 15x = 9 - 5
0x = 4
PROBLEM SOLVING METHOD NO. 2 -
We will first make ( x ) the subject in the first equation and solve accordingly.
Equation No. 1 -
5x = - 5 - y
x = ( 5 - y ) / 5
From this, we will substitute the value of ( x ) from the first equation into the second equation to solve for ( y ) accordingly.
Equation No. 2 -
- 15x - 3y = 9
- 15 [ ( 5 - y ) / 5 ] - 3y = 9
[ ( - 75 + 15y ) / 5 ] - 3y = 9
- 15 + 3y - 3y = 9
3y - 3y = 9 + 15
0y = 24
FINAL ANSWER:
Both problem solving methods show that the problem doesn't have a unique solution. The system is inconsistent.
Hope this helps! :)
Have a lovely day! <3